Biosafety Measures, Socio-Economic Impacts and Challenges of Bt-brinjal Cultivation in Bangladesh - Haque, Muhammad Shahidul; Saha, Nihar Ranjan (Frontiers in Bioengineering and Biotechnology, 2020)
This study surveyed the onsite biosafety measures adopted by the farmers cultivating Bt-brinjal, the socio-economic impact, and the challenges of Bt-brinjal cultivation in Bangladesh through interviews of 101 farmers from 26 Upazila (administrative region) under 20 Districts. Bangladesh Agricultural Research Institute (BARI) released Bt-brinjal 2 is popularly cultivated by 35% farmers. It was revealed that 52% of farmers maintained border crops. Among the growers, 52% informed that they disclose to the buyers that they are selling Bt-brinjal while selling in the open market where no product is traditionally labelled. Most of the farmers (71%) use Bt-brinjal plant debris as animal feed. Farmers (60%) received training on biosafety of Bt-brinjal cultivation. According to 85% of farmers, Bt-brinjal cultivation improved insect control. The farmers (77%) agreed that Bt-brinjal reduced labour and chemical costs and 75% of the farmers found increased yield and 72% of them found enhanced income by Bt-brinjal cultivation. However, 25% farmers informed that they did not get increased yield due to incidence of secondary insects. Most of the consumers (89%) believe that cultivation of Bt-brinjal improved quality of brinjal. Furthermore, 59% of the consumers opined that price was reduced due to Bt-brinjal cultivation. The consumers also believe that Bt-brinjal cultivation reduced pesticide use (97%) and concern of insecticide use (96%) and hence they consider Bt-brinjal safer for human health (96%). However, to harvest the benefits of modern biotechnology, proper management of the biosafety in Bt-brinjal cultivation and labelling of Bt-brinjal during marketing should be maintained properly.